Law and Religion in the Roman Republic - Tellegen-Couperus, Olga. (Leiden : BRILL, 2011)
Drawing on epigraphic, legal, literary, and numismatic sources, this book reveals how, in the Roman Republic, law and religion interacted to serve the same purpose, the continued growth and consolidation of Rome's power.
Divine law and the penalty of sacer esto in early Rome / Leon ter Beek -- Law and divination in the later republic / Federico Santangelo -- The curiate law and the religious nature of the power of Roman magistrates / Michel Humm -- Rationalizing religious practices : the pontifical calendar and the law / Jorg Rupke -- The jurisdiction of the pontiffs at the end of the fourth century BC / Jan Hendrik Valgaeren -- The longevity of the fetial priests / Linda Zollschan -- Sacred law and civil law / Olga Tellegen-Couperus -- The control of the sacred in Roman law / James Rives -- The immortality of the soul and Roman law / Jan Willem Tellegen.
Print version record.
Includes bibliographical references and index.
Keywords: Ecclesiastical law -- Rome; Priests -- Legal status, laws, etc. -- Rome; Religion and law -- Rome; Religion and state -- Rome; Rome -- Religion; Religion and law -- Rome; Religion and state -- Rome; Ecclesiastical law -- Rome; Priests -- Legal status, laws, etc. -- Rome; Rome -- Religion; LAW -- Administrative Law & Regulatory Practice; Electronic books; Electronic books